Transisi Paradigmatik Korporasi dan Konstruksi Pertanggung Jawaban Kejahatan Korporasi Era Globalisasi - Fajar Dian Aryani (Universitas Muhammadiyah Purwokerto, 2021)
Globalization cannot be separated from corporations. The development of the corporation through its products has been able to